Universal Design Principles for Multimodal Representation in Literacy Activities for Preschoolers. Issue 1 (February 2023) - Fundelius, Erika; Wade, Taryn; Robbins, Audrey; Wang, Sen; McConomy, M. Addie; Fumero, Keisey
The article demonstrates how to use the multimodal and multisensory representation principle of Universal Design for Learning (UDL) to increase access to storybook reading for diverse groups of preschoolers with extensive support needs (ESN). Storybook reading is an essential part of instruction in early childhood education. Utilizing UDL-inspired book boxes, children of all ability levels can partake in the activity in a meaningful manner. Multimodal representation, such as use of tangible or abstract items (e.g.: photos, miniatures, real items) or sensory experiences (e.g.: essential oils, food items, braille, physical movement) allow children to engage with stories in an enhanced manner. Book boxes can assist in developing concepts related to social emotional growth, social skills, functional living skills, environmental concepts, and vocabulary presented in books.